Oral Tradition as Context for Learning Music From 4E Cognition Compared With Literacy Cultures. Case Studies of Flamenco Guitar Apprenticeship - Casas-Mas, Amalia; Pozo, Juan Ignacio; Montero, Ignacio (Frontiers in Psychology, 2022)
The awareness of the last twenty years about embodied cognition is directing multidisciplinary attention to the musical domain and impacting psychological research approaches from the 4E cognition. Based on previous research regarding musical teaching and learning conceptions of 30 young guitar apprentices of advanced level in three learning cultures: Western classical, jazz, and flamenco of oral tradition, two participants of flamenco with polarized profiles of learning (reproductive and transformative) were selected as instrumental cases for a prospective ex post facto design. Discourse and practice of the two flamenco guitarists were analyzed in-depth to describe bodily issues and verbal discourse on the learning practice in their natural contexts. Qualitative analysis is performed on the posture, gestures, verbal discourse, and musical practice of the participants through the System for the Analysis of Music Teaching and Learning Practices (SAPIL). The results are organized attending a) the Embodied mind through differential postures and gestures of flamenco participants that showed a fusion among verbal, body language, and musical discourse with respect to the musical literacy cultures; b) the Embedded mind and a detailed description of circumstances and relationships of the two flamenco participants, and how music is embedded in their way of life, family and social context, and therefore transcends musical activity itself; c) the Enactive mind, regarding the active processes that make differences between the reproductive and the transformative flamenco apprentices, then tentative relationship are observed in the discourse of each apprentice and the way in which they practice; and finally, d) the Extended mind through the bodily, technical and symbolic tools they use during learning. Flamenco culture of oral tradition made use of listening, and temporary external representations instead of notational, but also the body played a central role in a holistic rhythm processing through multimodality, such as singing, playing, and dancing. Conclusions point out the embodied mind as a result of the culture of learning reflected through the body and the gesture in instrumental learning.